Reliability Measurement of Torque Transmission System for Spice Manufacturing Plant - Rao, Jivan; Sarip, Shamsul; Nabil Muhtazaruddin, Mohd; Armiza Mohd Aris, Siti; Azlan suhot, Mohamed; Zaki Hassan, Mohamad; Mohammad, Roslina; Yusof Md Daud, Mohd; Abdul Aziz, Saâ€™ardin; Aini Bani, Nurul; Mad Kaidi, Hazilah; Mohamed Kutty, Rasheed; et al. (International Journal of Engineering and Technology, 2019)
Growths of present day industries are forced towards the use of automation and more complex system. Currently, the manufacturing line that makes up with thousands of complicated components and make any failure of one or more components may affect the entire production system. In order to deal with this issue, preventive maintenance scheduling that to keep the machinery downtime as low as possible while reducing maintenance cost becomes a challenge to the process industry. In this regards, many factors such as maintenance practice, availability of maintenance repair & overhaul (MRO) spare parts and skilled of labor plays a major role to lead the industry stable and running at optimum condition. This paper presents the comparison breakdown frequency, and production output between belt driven, and gearbox driven vertical roller mill. In this study, the reliability for torque transmission system that used in for spice-based food industry has been evaluated. The breakdown cost and the reliability data were evaluated. In addition, the mean-time between failure (MTBF) and mean time to repair (MTTR) for critical components that significantly suggested for the preventive maintenance strategy were also calculated. With lesser failure frequency and more reliable availability of 99.47% as compared to 96.81% of gear box driven mill, the belt drive is concluded as the most effective drive system for pendulum roller mills.Â Â